Assessment of serum biomarkers and coagulation/fibrinolysis markers for prediction of neurological outcomes of out of cardiac arrest patients treated with therapeutic hypothermia - Park, Jeong Ho; Wee, Jung Hee; Choi, Seung Pill; Oh, Jae Hun; Cheol, Shin (Clinical and experimental emergency medicine, 2019)
Despite increased survival in patients with cardiac arrest, it remains difficult to determine patient prognosis at the early stage. This study evaluated the prognosis of cardiac arrest patients using brain injury, inflammation, cardiovascular ischemic events, and coagulation/fibrinolysis markers collected 24, 48, and 72 hours after return of spontaneous circulation (ROSC). From January 2011 to December 2016, we retrospectively observed patients who underwent therapeutic hypothermia. Blood samples were collected immediately and 24, 48, and 72 hours after ROSC. Neuron-specific enolase (NSE), S100-B protein, procalcitonin, troponin I, creatine kinase-MB, pro-brain natriuretic protein, D-dimer, fibrin degradation product, antithrombin-III, fibrinogen, and lactate levels were measured. Prognosis was evaluated using GlasgowPittsburgh cerebral performance categories and the predictive accuracy of each marker was evaluated. The secondary outcome was whether the presence of multiple markers improved prediction accuracy. A total of 102 patients were included in the study: 39 with good neurologic outcomes and 63 with poor neurologic outcomes. The mean NSE level of good outcomes measured 72 hours after ROSC was 18.50 ng/mL. The area under the curve calculated on receiver operating characteristic analysis was 0.92, which showed the best predictive power among all markers included in the study analysis. The relative integrated discrimination improvement and categoryfree net reclassification improvement models showed no improvement in prognostic value when combined with all other markers and NSE (72 hours). Although biomarker combinations did not improve prognostic accuracy, NSE (72 hours) showed the best predictive power for neurological prognosis in patients who received therapeutic hypothermia.